Mid‐Term Outcomes of Navigation‐Assisted Primary Total Knee Arthroplasty Using Adjusted Mechanical Alignment - Kai Zheng; Houyi Sun; Weicheng Zhang; Feng Zhu; Jun Zhou; Rongqun Li; Dechun Geng; Yaozeng Xu (Orthopaedic Surgery, 2023)
Objective The adjusted mechanical alignment (aMA) technique is an extension of conventional mechanical alignment (MA), which has rarely been reported. The purpose of this study was to evaluate mid‐term outcomes of navigation‐assisted total knee arthroplasty (TKA) using aMA. Methods This retrospective cohort study enrolled 63 consecutive patients (77 knees) who underwent navigation‐assisted TKA using aMA between September 2017 and October 2019. Fifty‐two consecutive patients (61 knees) who underwent TKA using MA during the same period were assessed as the controlled group. The demographic data and perioperative data were recorded. The parameters of resection and soft tissue balance including tibia resection angle, frontal femoral angle, axial femoral angle, joint line translation, medial and lateral gap in extension and flexion position were recorded. Radiographic parameters and functional scores including the Hospital for Special Surgery (HSS) score, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score, and Forgotten Joint Score‐12 (FJS‐12) were evaluated. Surgery‐related complications were recorded. The average follow‐up was 3.5 years, with a minimum of 2.4 years. Results The frontal femoral angle was 2.55° ± 1.08° in aMA group versus 0.26° ± 0.60° in MA group (p < 0.001). The axial femoral angle was 3.07° ± 2.23° external in aMA group versus 2.30° ± 1.70° in MA group (p = 0.027). The lateral flexion gap was wider in the aMA group, with a mean of 0.71 mm more laxity (p = 0.001). Postoperative coronal alignment was 177.03° ± 1.82° in aMA group versus 178.14° ± 1.69° in MA group (p < 0.001). The coronal femoral component angle was 92.62° ± 2.78° in aMA group versus 90.85° ± 2.01° in MA group (p < 0.001). Both aMA‐TKA and MA‐TKA achieved satisfactory mid‐term clinical outcomes. However, the HSS scores at 1 month postoperatively were significantly higher using aMA than using MA (p < 0.001). Conclusion Navigation‐assisted TKA using aMA technique obtained satisfactory mid‐term clinical outcomes. The aMA technique aims to produce a biomimetic wider lateral flexion‐extension gap and minimize releases of soft tissues, which might be associated with better early clinical outcomes than MA technique.